The restoring filter for analog interfaces of industrial information-measuring systems - Бороденко, І.А.; Куц, Ю.В.; Орнатський, Д.П. (Proceedings of National Aviation University (archive), 2005)
Problems of existing analog interfaces of industrial information-measuring systems are considered. The system of transfer of analog signals from a set of gauges to reception system of processing of results for the industrial test bench is offered. The most widespread restoring filters are compared to filters on the basis of iterative integrating converters.